2016
DOI: 10.1016/j.nano.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking and exocytosis of a multi-component siRNA nanocomplex

Abstract: Despite the importance of siRNA delivery systems, understanding of their intracellular fate remains elusive. We recently developed a multi-component siRNA nanocomplex to deliver siRNA to hepatic stellate cells (HSCs). The objective of this study is to study post internalization trafficking of this siRNA nanocomplex and its multiple components like siRNA, protamine, and streptavidin, in HSCs. After internalization, the nanocomplex entrapped in early endosomes undergoes three possible routes including endosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 46 publications
7
44
0
1
Order By: Relevance
“…In the end of the study, the rats were euthanized, and the serum and liver were harvested. [16] Herein, we also observed downregulation of type I collagen mRNA in the liver after treatment with the PCBP2 siRNA nanocomplex ( Figure 6D). In comparison to healthy rats, CCl 4 induction dramatically increased ALT and AST values to 500 IU L −1 and 464 IU L −1 , respectively, indicating significant inflammation and damage in the liver.…”
Section: Pcbp2 Sirna Nanocomplex Reverses CCL 4 -Induced Liver Fibrossupporting
confidence: 51%
See 2 more Smart Citations
“…In the end of the study, the rats were euthanized, and the serum and liver were harvested. [16] Herein, we also observed downregulation of type I collagen mRNA in the liver after treatment with the PCBP2 siRNA nanocomplex ( Figure 6D). In comparison to healthy rats, CCl 4 induction dramatically increased ALT and AST values to 500 IU L −1 and 464 IU L −1 , respectively, indicating significant inflammation and damage in the liver.…”
Section: Pcbp2 Sirna Nanocomplex Reverses CCL 4 -Induced Liver Fibrossupporting
confidence: 51%
“…We previously demonstrated that silencing PCBP2 in HSCs reduced the half-life of type I collagen mRNA and subsequently downregulated the amount of the mRNA. [16] Herein, we also observed downregulation of type I collagen mRNA in the liver after treatment with the PCBP2 siRNA nanocomplex ( Figure 6D). This downregulation is the key for the regression of accumulated ECM in fibrotic liver.…”
Section: Pcbp2 Sirna Nanocomplex Reverses CCL 4 -Induced Liver Fibrossupporting
confidence: 51%
See 1 more Smart Citation
“…The issue of toxicity is also very important 41 . Phagocytic uptake by the mononuclear phagocyte system in the bloodstream is a major challenge when using nanoparticles for siRNA delivery, which forces the use of chemical shields (for example, polyethylene glycol [PEG]) to prevent recognition 42 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2B, the biotinylated siRNA and biotinylated cholesterol anchored to the streptavidin backbone provide efficient silencing of the PCBP2 gene for liver fibrosis treatment. [57, 58] Streptavidin-biotin technology has also been utilized for the delivery of Kv1.3 siRNAs in the treatment of autoimmune disorders. Biotinylated polyethylene glycol and cholesterol were functionalized with biotinylated-CD45RO antibodies through the use of streptavidin to provide highly specific targeting and uptake of nanoparticles by Memory T cells, which had the consequence of decreasing the calcium ion influx, thus producing a therapeutic effect.…”
Section: Applications In Nanoscale Delivery Systemsmentioning
confidence: 99%